AB0688 Anti-C1Q antibody as a biomarker for systemic lupus erythematosus. (23rd January 2014) - Cόrica, M.E.; Lopez Sanchez, G.; Moya Alvarado, P.; Sarmiento, M.; Diaz Torne, C.; Castellví, I.; Geli, C.; Laiz, A.; Diaz Lopez, C.; de Llobet, J.M.
Abstract : Background: SLE is the prototype of the autoimmune systemic disease. It is characterized by the production of autoantibodies against the cell nucleus components in association with multiple clinical manifestations that affect different organs 1 . There are studies that support the hypothesis that the components of the classic pathway of the complement are necessary to produce the phagocytic clearance of the apoptotic cells, which provides a possible explanation for the high frequency of SLE among patients with deficiencies of said components, especially C1q 2 . Approximately one third of the patients with SLE have high serum levels of anti-C1q antibodies 3 . Objectives: To observe the value of anti-C1q antibody as a biomarker in SLE. Methods: The clinical charts of 135 patients with SLE being followed up by the Rheumatology Unit of Hospital de la Santa Creu i Sant Pau and who had been tested to determine the presence of anti-C1q antibody were analyzed retrospectively. We studied clinical, hematological and immunological variables. Results: It was observed that patients with anti-C1q antibodies were younger at the time of disease onset (32.9 vs 44.8 years, p<0.005). We found a statistically significant relation between the presence of anti-C1q antibodies and some of the most recognized biomarkers of SLE: anti- DNAds ( p =0.034), anti- Sm( p =0.045), homogeneous ANA ( p =0.031) and low concentration of C3 complement ( p =0.006). As it was observed in previous studies, we found a higher frequency of lupus nephritis in anti-C1q positive patients but this difference was not statistically significant (38.9% vs 27.3%, p=0139). We observed that 8 out of 9 patients with vasculitis present anti-C1q antibodies establishing a statistically significant relation ( p <0.001). Conclusions: The anti-C1q antibodies have been associated with different clinical, hematological and immunological manifestations in patients with SLE, especially with lupus nephropathy, hypocomplementemia and leucopenia. Our results reflect partially what was published previously. We were able to observe that the anti-C1q positive patients present, in a statistically significant way, more positivity for anti-DNAds, anti-Sm y homogeneous ANA antibodies. With normal values of this biomarkers, the flares of SLE are rare. This could indicate that the presence of anti-C1q antibody is a factor of bad prognosis, both renal and globally. As it is confirmed in recent studies, the value of anti-C1q as a biomarker in lupus nephropathy should be taken with caution. However, its presence together with other biomarkers of SLE, could be helpful for the diagnosis References: Firestein GS, Budd RC, Harris Jr. ED, McInnes IB, Ruddy S, Sergent JS. Kelly's Textbook of Rheumatology; 2009, 8° ediciόn, Editorial Saunders Elsevier Crow MK. Developments in the clinical understanding of lupus. Arthritis Res Ther. 2009;11(5):245-56. Pickering MC, Botto M, Taylor PR, Lachmann PJ, Walport MJ. Systemic lupus erythematosus, complement deficiency, and apoptosis. Adv Immunol. 2000;76:227-324 Disclosure of Interest: None Declared